Fabrication and characterization of carbon and glass fiber reinforced thermoplastic composites by fused filament fabrication - Dilşad Akgümüş Gök; Berk Dinçer Akay (Scientific Reports)
Abstract Fused filament fabrication (FFF) is a widely used additive manufacturing (AM) technology due to its cost-effectiveness, material efficiency, and the ability to produce complex geometries. However, the mechanical limitations of thermoplastic materials limit their use in broader functional applications. In this study, PLA and ABS thermoplastics were reinforced with 1%, 3%, and 5% carbon fiber (CF) and glass fiber (GF) to improve their mechanical performance. The results showed that 3% reinforcement provided the most balanced performance overall. The highest tensile strength was 29.67 MPa in the ABS + 3%CF samples, while the highest tensile strength among the PLA composites was measured as 17.47 MPa in the PLA + 3%GF samples. The highest impact strength was obtained with 1% reinforcement for ABS and 5% reinforcement (0.47 J) for PLA-GF. While GF reinforcement increased stiffness in PLA, 5% reinforcement in both matrices caused a performance decrease due to fiber agglomeration. SEM–EDS and FTIR analyses supported optimal binding and dispersion at 1–3% reinforcement ratios. The increased strength, toughness, and structural integrity of the resulting 3% reinforced composites suggest that these materials are potential candidates for applications requiring lightweight and durable parts, such as those in the defense industry. Future studies are recommended to evaluate long-term performance criteria such as fatigue and environmental resistance, and to improve fiber distribution for higher reinforcement ratios.